The Role of Digital Communication in Dealing with Crises in the Work Environment for Employees in the State of Kuwait - Alyousef, Ameena Mahmoud Ghaith (The Arab Journal of Administration, 2025)
The current study aimed to reveal the role of digital communication in dealing with crises in the work environment among employees in the State of Kuwait, and to reveal the obstacles that employees may face when using digital communication in dealing with crises. A scale was developed to reveal digital communication among employees in dealing with crises in the work environment, and its psychometric properties were verified for validity and reliability. The sample was selected randomly, as the sample consisted of (180) male and female employees, including (90) male employees and (90) female employees. They were selected from employees in the College of Business Studies at the Public Authority for Applied Education and Training in 2024. The descriptive analytical approach was used. The results of the study indicated that the level of digital communication and the role of employees in dealing with crises in the work environment, whether from a social, cognitive, or cultural perspective, was at an average level. The obstacles that employees suffer from in digital communication when dealing with crises in the work environment were at an average level. There were no differences between males and females in digital communication, whether from a social or cultural perspective, while there were differences in favor of females in digital communication from a cognitive perspective, as indicated by Males face more obstacles in digital communication than females. Based on the results of the study, some recommendations were made, including the need for various institutions to pay attention to developing modern digital communication strategies so that employees can use them more effectively in the event of crises in the work environment.